KAJIAN PERILAKU BERSEPEDA MOTOR DI JAKARTA - Chie, Ho Hwi; Widaningrum, Dyah Lestari (Industrial and Systems Engineering Assessment Journal (INASEA), 2014)
This study aims to test the hypothetical model that describes the correlation between motorcycling behavior and four latent variables assumed to make up bikers in action. A survey of 350 motorcyclists through purposive sampling was done by employing a research instrument. Validity and reliability test of research instrument were conducted by calculating the Cronbachs Alpha. Whereas, the hypothesis model test was conducted using statistical technique of Structural Equation Modeling (SEM) through Lisrel 8.72 software. CFI, Chi-square, and RMSEA are fit indexes used to test the suitability of the hypothesis model with field data (model fit). Structural Equation Modeling (SEM) and Confirmatory Factor Analysis (CFA) were used to evaluate the reliability and structural validity of the instrument used. Besides, they were used to test the hypothesis that a positive relationship between the observed variables and the four latent variables, as well as a positive relationship between the four latent variables and motorcycling behavior construct.